Peran Media Sosial dalam Strategi Komunikasi Pemasaran: Analisis Efektivitas dan Implementasi - Saraan, Muhammad Rasyad Ghazali; Arwansyah, OK Dedi; Fatmawati, Eka; Suharyanto, Agung (Mahesa Research Center, 2025)
This study aims to analyze the effectiveness of marketing communication strategies through social media in increasing sales, brand awareness, and customer loyalty. Using a quantitative approach with a survey method, data was collected from e-commerce, retail, and service companies that actively use social media, as well as interviews with digital marketing experts. The results show that quality content-based strategies, the use of influencers or Key Opinion Leaders (KOLs), and consistent brand identity can increase engagement up to 60% higher than conventional advertising, while content-based marketing strategies can increase brand recall by 80%. However, challenges such as changes in social media algorithms, increasing digital advertising costs, and competition in building authentic customer engagement need to be overcome for the strategy to run effectively. Evaluation based on engagement rate (user interaction with content), conversion rate (percentage of visitors who make a purchase), and return on investment (ROI) from digital campaigns are key in optimizing digital marketing strategies. With the right adjustments, social media can be an effective and sustainable marketing tool, positively impacting business growth in the digital age.